Exploring the Impact of Quality Housekeeping Services on Customer Satisfaction and Revisit Intentions: A Study of Luxury Hotels in Uttar Pradesh - Ojha, Uma Rajey Shukla; Gupta, Nimish; Tiwari, Munish Kumar; Srivastava, Alpna; Singh, Rashika (International Review of Management and Marketing, 2025)
This study investigates the impact of various dimensions of housekeeping service quality on customer satisfaction and revisit intention in the hospitality industry. Specifically, it explores the roles of Attention to Detail, Cleanliness of Room, Professionalism of Housekeeping Staff, Perceived Service Quality, Room Amenities, and Timeliness of Housekeeping. A conceptual model was tested using path analysis to examine both direct and indirect relationships between these dimensions and customer satisfaction, with customer satisfaction serving as a mediator between service quality and revisit intention. The study used survey data collected from hotel guests, analysing the relationships among constructs using structural equation modelling (SEM). The results revealed that all hypothesized paths were statistically significant, with customer satisfaction playing a central role in mediating the relationship between housekeeping service quality and revisit intention. Among the dimensions of service quality, Perceived Service Quality and Timeliness of Housekeeping showed the strongest positive effects on customer satisfaction. Additionally, the direct effect of customer satisfaction on revisit intention was notably high, confirming its importance as a predictor of repeat customer behaviour. Indirect effects were also significant, highlighting the importance of maintaining high standards in all aspects of housekeeping to ensure customer satisfaction and encourage return visits. The findings have important implications for hotel managers, emphasizing the need to prioritize dimensions such as Perceived Service Quality and Timeliness of Housekeeping to enhance customer satisfaction and increase customer loyalty. The study also provides valuable insights into the complex relationships between service quality, customer satisfaction, and revisit intention, offering practical recommendations for service improvements. However, the study is limited by its cross-sectional nature and the focus on a single industry context. Future research could explore longitudinal effects and cross-industry comparisons to further validate and extend.